PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KEARIFAN LOKAL PEMBELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA DI KELAS IV SDN 06 SITIUNG - Ahmad Ilham Asmaryadi; Eka Eliza; Eka Filahanasari (Jurnal Binagogik, 2025)
This research aims to develop a student worksheet (LKPD) based on local wisdom for the subject "My Indonesia is Rich in Culture" for fourth-grade students. This study was conducted due to the lack of student interest in learning and the monotonous learning process, which is still teacher-centered and relies solely on textbooks or worksheets, resulting in low student engagement. Therefore, the objective of this research is to develop a Local Wisdom-Based LKPD for the IPAS subject on the topic "My Indonesia is Rich in Culture" for Grade IV students at SDN 06 Sitiung. The research method used is Research and Development (R&D) with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The types of data used are both qualitative and quantitative. The instruments developed include validation sheets, practicality sheets, and effectiveness sheets. Data collection techniques include observation, interviews, tests, and documentation. The data analysis techniques used are validity analysis, practicality analysis, and effectiveness analysis. The validation results from three validators indicate that the LKPD meets the validity criteria in terms of content, graphics, and language, with validity percentages of 102% (very valid), 80% (valid), and 90% (very valid), respectively. The practicality test by the fourth-grade teacher shows that the LKPD is very practical to use, with a score of 63 and a percentage of 96%. The effectiveness test shows that 17 out of 19 students (88.89%) achieved scores above the minimum mastery criteria (KKTP) after using the LKPD. Therefore, the developed LKPD learning media is declared valid, practical, and effective.